The Using of GIS to Delineate the Liquefaction Susceptibility Zones at Yogyakarta International Airport - Nicholas Hartono; Teuku Faisal Fathani (Institute of Research and Community Outreach - Petra Christian University, 2022)
Spatial analysis is performed to delineate liquefaction susceptibility zones at Yogyakarta International Airport(YIA). The low to medium cohesionless soil consistency is predominantly observed on the upper subsoil. A shallow groundwater level and low fines content have also enlarged the likelihood of earthquake-induced liquefaction. An SPT based liquefaction triggering procedure is adopted in this study to indicate the Factor of Safety (FoS) whereas the Liquefaction Severity Index (LSI) is used to measure the severity of liquefaction by presuming its manifestation. Inverse Distance Weighted (IDW) interpolation in QGIS is chosen to produce a map with 50 m × 50 m grid size. The analysis results show the YIA’s area is prone to undergo liquefaction at various depths. However, thin liquefied layers may not generate sufficient artesian flow pressure to eject water or sand. The LSI analysis concludes that YIA area is categorized as a non-liquefied to moderate severity where the West side is the governing area